Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1080/01431161.2017.1283074
|View full text |Cite
|
Sign up to set email alerts
|

Estimating vertical canopy cover using dense image-based point cloud data in four vegetation types in southern Sweden

Abstract: This study had the aim of investigating the utility of image-based point cloud data for estimation of vertical canopy cover (VCC). An accurate measure of VCC based on photogrammetric matching of aerial images would aid in vegetation mapping, especially in areas where aerial imagery is acquired regularly. The test area is located in southern Sweden and was divided into four vegetation types with sparse to dense tree cover: unmanaged coniferous forest; pasture areas with deciduous tree cover; wetland; and manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
(56 reference statements)
0
11
0
Order By: Relevance
“…The inter-comparison of selected algorithms for the purposes of producing point clouds for forest attribute prediction has typically focused on a comparison of two software packages, rather than a systematic evaluation. Ullah et al [48] and Kukkonen et al [68] compared software in the context of the ABA for forest attributes, for canopy cover prediction by Granholm et al [76], and for miscellaneous targets in Remondino et al [45]. Both Ullah et al [48] and Kukkonen et al [68] found that data derived from image-matching techniques were capable of predicting forest inventory attributes with comparable accuracies to those from ALS, which is the consensus from other comparative analyses [42,58,77].…”
Section: Image-matching Algorithmsmentioning
confidence: 90%
See 1 more Smart Citation
“…The inter-comparison of selected algorithms for the purposes of producing point clouds for forest attribute prediction has typically focused on a comparison of two software packages, rather than a systematic evaluation. Ullah et al [48] and Kukkonen et al [68] compared software in the context of the ABA for forest attributes, for canopy cover prediction by Granholm et al [76], and for miscellaneous targets in Remondino et al [45]. Both Ullah et al [48] and Kukkonen et al [68] found that data derived from image-matching techniques were capable of predicting forest inventory attributes with comparable accuracies to those from ALS, which is the consensus from other comparative analyses [42,58,77].…”
Section: Image-matching Algorithmsmentioning
confidence: 90%
“…They found negligible differences in generated digital surface models and indicated that both algorithms were capable, accurate, and consistent (±~2% RMSE for all attributes) at providing forest attribute predictions with the pre-condition that an ALS DTM was available. Granholm et al [76] compared the MATCH-T and SURE algorithms for estimating vertical canopy cover and found differences in point cloud outputs, but not in generated metrics. All studies, however, were cautious in their recommendation of a particular algorithm due to the potential differences that could arise from software tuning, forest type, and solar illumination.…”
Section: Image-matching Algorithmsmentioning
confidence: 99%
“…UAS products commonly use cm-level resolution and have high accuracy [19]. During recent years, the use of UAS in forestry has increased rapidly due to the advantages of low-cost, flexibility, and repeatability, for example in forest inventory parameters (e.g., tree location, tree height, crown width, and volume) estimation [20,21], forest change and recovery monitoring [22,23], canopy cover estimation [24,25], and individual tree crown segmentation [26,27]. UAS makes the on-demand acquisition of multiple temporal and high spatial resolution imagery possible [28].…”
Section: Introductionmentioning
confidence: 99%
“…Analysing trends in the experiments, better results and relationships between direct measurements from a botanical campaign were for individuals with a large crown and great crown density, depending on the tree and shrub species. Granholm et al [58] also indicated that the accuracy of tree heights estimated using semiglobal matching (SGM) is low when canopy cover values are low. Regarding LIDAR technology, which also provides a CHM, Leckie et al [59] achieved better results, similar to terrain measurements, when the tree density is higher.…”
Section: Discussionmentioning
confidence: 99%